Motif content comparison between monocot and dicot species - Matyas Cserhati (Genomics Data, 2015)
While a number of DNA sequence motifs have been functionally characterized, the full repertoire of motifs in an organism (the motifome) is yet to be characterized. The present study wishes to widen the scope of motif content analysis in different monocot and dicot species that include both rice species, Brachypodium, corn, wheat as monocots and Arabidopsis, Lotus japonica, Medicago truncatula, and Populus tremula as dicots. All possible existing motifs were analyzed in different regions of genomes such as were found in different sets of sequences in these species: the whole genome, core proximal and distal promoters, 5′ and 3′ UTRs, and the 1st introns. Due to the increased number of species involved in this study compared to previous works, species relationships were analyzed based on the similarity of common motif content. Certain secondary structure elements were inferred in the genomes of these species as well as new unknown motifs. The distribution of 20 motifs common to the studied species were found to have a significantly larger occurrence within the promoters and 3′ UTRs of genes, both being regulatory regions. Motifs common to the promoter regions of japonica rice, Brachypodium, and corn were also found in a number of orthologous and paralogous genes. Some of our motifs were found to be complementary to miRNA elements in Brachypodium distachyon and japonica rice.